The cupping therapy along meridian in treating one case of stiff neck and related nursing management (循经拔罐治疗落枕1例的中医特色护理体会) - ZHAO Xin (赵欣); GAI Chen (盖晨); LIU Huan (刘欢); XU Yaqi (徐雅琪); XU Weihong (徐卫红); SHANG Zhihua (尚志花); WANG Chunhong (王春红); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the nursing experience of cupping therapy along meridian in treating one case of stiff neck. The cupping therapy was carried out along meridian and acupoint which reflects the painful area according the syndrome differentiation. Nurses had enhanced the observation on patient reactions during the cupping treatment. The cupping therapy is an easy-to-operate technique and effective to relieve the stiff neck-assoicated symptoms. (本文总结1例运用循经拔罐治疗落枕患者的护理经验, 首先通过辨证选穴, 根据疼痛部位循经行罐, 然后在相关穴位留罐, 施行期间注意观察患者反应, 以患者耐受为宜。循经拔罐能有效缓解患者落枕症状, 且操作简便, 充分了体现中医护理特色, 值得临床参考。)